Doping top-down e-beam fabricated germanium nanowires using molecular monolayers. (May 2017) - Long, B.; Alessio Verni, G.; O'Connell, J.; Shayesteh, M.; Gangnaik, A.; Georgiev, Y.M.; Carolan, P.; O'Connell, D.; Kuhn, K.J.; Clendenning, S.B.; Nagle, R.; Duffy, R.; et al.
Abstract: This paper describes molecular layer doping of Ge nanowires. Molecules containing dopant atoms are chemically bound to a germanium surface. Subsequent annealing enables the dopant atoms from the surface bound molecules to diffuse into the underlying substrate. Electrical and material characterization was carried out, including an assessment of the Ge surface, carrier concentrations and crystal quality. Significantly, the intrinsic resistance of Ge nanowires with widths down to 30 nm, doped using MLD, was found to decrease by several orders of magnitude.